Who is One Locus Mismatched sibling Donor, Who is not? - Mohammadreza Ostadali (International Journal of Hematology-Oncology and Stem Cell Research, 2009)
"nThe most important factor in donor-recipient matching for hematopoietic stem cell transplantation is their HLA typing. "nFor many patients, we can not find a full-matched donor. In high risk patients, one locus mismatched related donors are suitable alternatives. (1, 2) "nSince the matching of patients and their siblings usually is based on low resolution HLA typing, the matching of one locus mismatched siblings is always prone to catastrophic errors. "nThe following cases clearly demonstrate the possible pitfalls and highlight the importance of the HLA typing of parents in the matching of patients and their full-matched and one locus, mismatched siblings.